Normalization of Neuroinflammation: A New Strategy for Treatment of Persistent Pain and Memory/Emotional Deficits in Chronic Pain - Liu XG (Dove Medical Press, 2022)
Xian-Guo Liu Pain Research Center and Department of Physiology, Zhongshan School of Medicine of Sun Yat-sen University, Guangzhou, People's Republic of ChinaCorrespondence: Xian-Guo Liu, Pain Research Center and Department of Physiology, Zhongshan School of Medicine of Sun Yat-sen University, 74 Zhongshan Road2, Hemulou 806, Guangzhou, 510080, People's Republic of China, Tel/Fax +86 87331956, Email liuxg@mail.sysu.edu.cnAbstract: Chronic pain, which affects around 1/3 of the world population and is often comorbid with memory deficit and mood depression, is a leading source of suffering and disability. Studies in past decades have shown that hyperexcitability of primary sensory neurons resulting from abnormal expression of ion channels and central sensitization mediated pathological synaptic plasticity, such as long-term potentiation in spinal dorsal horn, underlie the persistent pain. The memory/emotional deficits are associated with impaired synaptic connectivity in hippocampus. Dysregulation of numerous endogenous proteins including receptors and intracellular signaling molecules is involved in the pathological processes. However, increasing knowledge contributes little to clinical treatment. Emerging evidence has demonstrated that the neuroinflammation, characterized by overproduction of pro-inflammatory cytokines and glial activation, is reliably detected in humans and animals with chronic pain, and is sufficient to induce persistent pain and memory/emotional deficits. The abnormal expression of ion channels and pathological synaptic plasticity in spinal dorsal horn and in hippocampus are resulting from neuroinflammation. The neuroinflammation is initiated and maintained by the interactions of circulating monocytes, glial cells and neurons. Obviously, unlike infectious diseases and cancer, which are caused by pathogens or malignant cells, chronic pain is resulting from alterations of cells and molecules which have numerous physiological functions. Therefore, normalization (counterbalance) but not simple inhibition of the neuroinflammation is the right strategy for treating neuronal disorders. Currently, no such agent is available in clinic. While experimental studies have demonstrated that intracellular Mg2+ deficiency is a common feature of chronic pain in animal models and supplement Mg2+ are capable of normalizing the neuroinflammation, activation of upregulated proteins that promote recovery, such as translocator protein (18k Da) or liver X receptors, has a similar effect. In this article, relevant experimental and clinical evidence is reviewed and discussed.Keywords: ion channels, synaptic plasticity, cytokine, glial cell, monocytes